Evaluating the Adoption of AI Systems and Technologies in Zimbabwean Businesses: Case of Masvingo Town - Ivy Jean Marima; Florence Chekera; Samuel Mukute, (African Journal of Education,Science and Technology (AJEST), 2025)
Artificial intelligence is being adopted worldwide and is changing the industrial landscape. Supermarkets are not being left out. Tasks that previously needed human intelligence are now being performed by Artificial Intelligence using models and robots. The study evaluated the level of adoption of Artificial Intelligence by businesses in Zimbabwe to comprehend the present shape of AI adoption and its hindrances. The study investigated the Extent of Artificial Intelligence adoption assessing the level of adoption of Artificial Intelligence in various sectors of business in Zimbabwe. It will outline the major applications of Artificial Intelligence for example data analytics, automation, chat bots etc. It also assessed the potential benefits of using AI in business which included increased customer-supplier intimacy, reduced costs, increased efficiency and informed decision making. Challenges and obstacles hindering the rapid and widespread adoption of AI in Zimbabwean businesses were outlined and assessed. The study adopted a mixed research method which used quantitative and qualitative data collection techniques and analysis. Interviews and structured questionnaires were used to gather data. The population consisted of shop owners, managers, supervisors and operatives of supermarkets in Masvingo local business center. The study found out that the use of AI in businesses is on the down side at 29.55% where businesses using AI are focusing on the use of Enterprise Resource Planning Systems, Demand forecasting, chat bots, and online stores. The challenges cited by most businesses were lack of skilled personnel, infrastructure, financial capacity and awareness. The study recommends training of personnel, incorporating AI in business in the curriculum, enhancement of innovation culture, and financial capacitation of businesses.